Measuring teamwork quality in large‐scale agile organisations evaluation and integration of the aTWQ approach. Issue 6 (12th August 2021) - Poth, Alexander; Kottke, Mario; Riel, Andreas
Abstract: The maturity of organisations is measured using process assessment models like the International Organization for Standardization (ISO)/IEC 33001. Product quality is refined with internal and external product quality characteristics based on models like the ISO/IEC 25010. With the shift from the Tailorism‐driven process orientation to a more people‐centric organization, the process and product quality dimensions have to be extended by the teamwork quality (TWQ) dimension. For the sake of systematic organization development, this new third quality dimension needs to be integrated into existing quality frameworks to achieve a holistic quality approach. This article introduces agile TWQ as the method of choice. It explains its design, implementation and evaluation in the large enterprise context of the Volkswagen AG. It provides insights into the effectivity of this approach in heterogeneous multi‐team settings, as well as into its strengths, weaknesses, and limitations.